La2/3Sr1/3VO3 Thin Films: A New p‐Type Transparent Conducting Oxide with Very High Figure of Merit. (31st January 2018) - Hu, Ling; Wei, Renhuai; Yan, Jian; Wang, Dong; Tang, Xianwu; Luo, Xuan; Song, Wenhai; Dai, Jianmin; Zhu, Xuebin; Zhang, Changjin; Sun, Yuping
Abstract: Transparent conducting oxides (TCOs) are a unique series of materials combining electrical conductivity with optical transparency. Most of the commercially available TCOs are of the n‐type. The performance of p‐type TCOs, however, is far behind their n‐type TCO counterparts primarily due to the doping bottleneck and low hole mobility. Herein, a Mott–Hubbard insulator of LaVO3 is proposed as the starting point for exploring p‐type TCOs. Substitution of La 3+ by Sr 2+ can introduce high hole carrier concentration at the top of the valence band to overcome the doping bottleneck. Combining a modest carrier mobility with weak absorption in the visible region, La1‐ x Sr x VO3 compounds can serve as new p‐type TCOs and exhibit good balance of the tradeoffs between electrical conductivity and optical transparency. It is demonstrated that La2/3 Sr1/3 VO3 thin films exhibit a high conductivity of 742.3–872.3 S cm −1 at room temperature and a high transmission of 53.9–70.1% in the visible region, which leads to the highest figure of merit among p‐type TCOs so far. Abstract : La2/3 Sr1/3 VO3 thin films are reported as a new p‐type transparent conducting oxide with high performance. The good balance between electrical conductivity and optical transparency results in the highest figure of merit for p‐type transparent conducting oxide so far.